1994
DOI: 10.1148/radiology.190.2.8284391
|View full text |Cite
|
Sign up to set email alerts
|

Vesicoureteral reflux: an accurate predictor of acute pyelonephritis in childhood urinary tract infection?

Abstract: VUR (as shown by VCUG) and renal cortical scintigraphic defects frequently occur independently of each other. Renal cortical scintigraphy may be a more accurate predictor of patients at risk for scarring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
7

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 0 publications
1
32
0
7
Order By: Relevance
“…14 Children with APN are substantially vulnerable to renal scarring due to the necrosis and fibrosis associated with acute inflammation. Actually, it has been shown that 80% of defects in APN tend to remain unchanged at least 6 months after onset; 15 in fact the defects in a binary manner resolve or eventually turn into scars.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Children with APN are substantially vulnerable to renal scarring due to the necrosis and fibrosis associated with acute inflammation. Actually, it has been shown that 80% of defects in APN tend to remain unchanged at least 6 months after onset; 15 in fact the defects in a binary manner resolve or eventually turn into scars.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, nephrologists generally take some specific clinical signs, such as high fever, serious enough to order a diagnostic imaging test. 15 Other known factors 7 that increase the likelihood of renal damage in children have been shown to be reflux, CRP and body temperature. Obviously, the probability of renal damage in children suffering from UTI and high levels of CRP, high fever and dilating reflux is up to ten times higher than their counterpart with normal or slightly elevated CRP levels, no or mild fever, and no reflux.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Múltiples factores de riesgo como menor edad, alto grado de RVU, virulencia del microorganismo causante y retraso en el inicio del tratamiento antibiótico, han sido correlacionados con el desarrollo de cicatriz renal, sin embargo, la patogéne-sis de ella es aún muy controvertida 4,[12][13][14] .…”
Section: Discussionunclassified
“…Na última década vários trabalhos têm estudado as alterações encontradas na cintilografia renal com DMSA durante a PNA 14,[16][17][18][19][20][21][22] . Embora esses trabalhos variem em relação à população estudada, concordam nos seguintes aspectos: o dano ao parênquima renal é detectado pelo exame com DMSA durante a infecção aguda na maioria dos pacientes (50 a 80%) e o exame com DMSA alterado é raro em crianças com diagnóstico de cistite 23,24 .O objetivo deste estudo é analisar se a presença de alterações na cintilografia renal com DMSA na fase aguda da infecção urinária pode ser indicadora de pielonefrite.…”
unclassified